Strategies and Policies for Education: A Review - Neeraj Tiwari (AG Volumes, 2022)
The construction of an effective education policy is essential to enhancing the effectiveness of the service. The design is influenced by the dimensions of organizational environment, organizational principles, and organizational resources, all of which have an effect on the design in addition to the primary application of education approaches. Organizational resources have the greatest impact on the effectiveness of education services at Jayapura Regency, while the work environment has the least impact. The impact of the organizational environment is limited because of a tendency to neglect the importance of politics, geography, demography, and natural resources as components of the external environment. Along with this, the support supplied by organizational values and resources determines how education services are to be shaped and how they meet public demands.